Lamun Oceana serrulata Di Perairan Provinsi Kepulauan Bangka Belitung - Adi, Wahyu; Muftiadi, Muhammad Rizza; Pamungkas, Aditya; Henri, Henri; Robika, Robika; Supratman, Okto; Maharani, Maharani; Animah, Animah; Angelia, Fera; Haptari, Rapita; Emillia, Emillia (Journal of Tropical Marine Science, 2024)
Taxonomically, according to the World Register of Marine Species (WORMS), in 2021 the naming of the species Cymodocea serrulata will change to Oceana serrulata (R. Brown) Byng & Christenh. Many studies have been carried out in the Province of the Bangka Belitung Islands, but this type of distribution map has not been presented in detail. Observation of seagrass in the field allows the identification of seagrasses with other types of seagrass. This study aimed to identify morphology, species distribution, and other types of seagrass often associated with seagrass species Oceana serrulata in the Province of the Bangka Belitung Islands. The methods in this study include data collection, identification, and map making. Morphological identification of seagrass species refers to several identification sources. The distribution map of Oceana serrulata is presented from the seagrass data collection that has been carried out. This research uses data from different times, the first was obtained from 2011 and 2022 as primary data. The results of the study explain the identification carried out on the Oceana serrulata has the same characteristics as identification literature. Similarities seen from the identification of leaf morphology which ribbon curved like, parallel leaf veins and triangular shaped sheaths. Other seagrass species that are most often associated with Oceana serrulata are Halodule uninervis and Enhalus acoroides. The map of the distribution of seagrass species Oceana serrulata is found on the islands of Bangka, Belitung, Anak Air, Lepar, Ketawai, Semujur, Kalimambang, Kelayang, Kepayang, Ruk, and Sebongkok islands.